2022
DOI: 10.1021/acsaenm.2c00095
|View full text |Cite
|
Sign up to set email alerts
|

Self-Healable, Injectable, and Conductive Supramolecular Eutectogel for the Encapsulation and Sustained Release of the Anticancer Drug Curcumin

Abstract: The intriguing properties such as high environmental compatibility of supramolecular gels made solely through reversible noncovalent interactions are of recent interest. To offer proof of concept for the new-age sustainable materials, herein we have designed the self-healable, injectable, and ionic conductive supramolecular eutectogel in natural deep eutectic solvent (NADES). The studied eutectogels were prepared by dissolving the pharmaceutically active cetylpyridinium chloride (C 16 PyCl) and cetylpyridinium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 65 publications
1
11
0
Order By: Relevance
“…Our prior research involving Eutectogels created with C16PyCl and C16PyBr surfactants in different DESs exhibited gel-to-sol behavior below 15 % strain, underscoring the higher strength of polymeric eutectogels compared to surfactant-based eutectogels. [31] Moreover, Marullo et al observed that in supramolecular eutectogels, G" exceeded G' when the strain exceeded 1 % while the frequency remained at 1 rad/s, further supporting the superior mechanical strength of our polymeric eutectogel over amino acid-based eutectogels. [30] To assess injectability and self-recovery (self-healing) capabilities of the eutectogel, we conducted a thixotropic study (Figure 3c).…”
Section: Mechanical Strength Through Rheologysupporting
confidence: 64%
See 1 more Smart Citation
“…Our prior research involving Eutectogels created with C16PyCl and C16PyBr surfactants in different DESs exhibited gel-to-sol behavior below 15 % strain, underscoring the higher strength of polymeric eutectogels compared to surfactant-based eutectogels. [31] Moreover, Marullo et al observed that in supramolecular eutectogels, G" exceeded G' when the strain exceeded 1 % while the frequency remained at 1 rad/s, further supporting the superior mechanical strength of our polymeric eutectogel over amino acid-based eutectogels. [30] To assess injectability and self-recovery (self-healing) capabilities of the eutectogel, we conducted a thixotropic study (Figure 3c).…”
Section: Mechanical Strength Through Rheologysupporting
confidence: 64%
“…The findings suggest that the gel transforms into a sol form at strain levels greater than 15 %, aligning with established rheological gel behavior. Our prior research involving Eutectogels created with C16PyCl and C16PyBr surfactants in different DESs exhibited gel‐to‐sol behavior below 15 % strain, underscoring the higher strength of polymeric eutectogels compared to surfactant‐based eutectogels [31] . Moreover, Marullo et al.…”
Section: Resultsmentioning
confidence: 82%
“…We have further used the pair of probes ANS and R6G to calculate the radius of micellar aggregates through measuring the distance between these probes after adding them in aggregate system using Fluorescence Resonance Energy Transfer (FRET) [25] . As the emission spectra of ANS, overlaps with the excitation spectra of R 6 G [25b] …”
Section: Resultsmentioning
confidence: 99%
“…Regarding scaling up the process of obtaining these antioxidant glycosylated flavonoids from pepper biomass residues and their utilization as food additives and supplements, it is necessary to recover the metabolites from the crude extract. Alternatively, we propose to overcome this issue by utilizing the whole NaDES containing phytochemicals as liquid active ingredients or additives in functional materials. , For instance, there are examples in the literature where the extracts (phytochemical-containing NaDES) are used as pharmaceutic dosage forms, in the form of eutectogels (gels formed by the addition of a gelling agent, typically a (bio)­polymer, to a NaDES), creams, and ointments, among others . This is possibly due to the low toxicity of the NaDESs, whose components can also present pharmacological or biological activities, e.g., therapeutic DES (THEDES). , …”
Section: Resultsmentioning
confidence: 99%